Implementasi Algoritma Kriptografi Hybrid AES dan RSA dalam Rancang Bangun Aplikasi Bank Sampah Pancadaya Berbasis Web untuk Keamanan Data Transaksi Nasabah - Mardhyah Fathania ‘Izzati; Widya Darwin (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This research aims to develop a transaction data security system on the web-based Pancadaya Waste Bank application by applying a hybrid cryptographic algorithm that combines Advanced Encryption Standard (AES) and Rivest Shamir Adleman (RSA). The problem faced in the previous system is the weak recording and security of customer transaction data, because the process is still carried out manually so that it is prone to recording errors, loss of important information, and potential misuse of data by unauthorized parties. To answer these problems, this study uses the Rapid Application Development (RAD) method which allows the application development process to be carried out quickly, flexibly, structured, and according to user needs. The research method used was a qualitative approach with interview techniques with the management of the Pancadaya Waste Bank and the Environment Office, as well as an in-depth literature study on the application of hybrid cryptographic algorithms in modern information systems. The system is built using the PHP programming language, MySQL database, and OpenSSL library as the main support for the data encryption and decryption process. The implementation of the algorithm is carried out by encrypting transaction data using AES for efficiency and speed, then the AES key is secured through RSA to ensure a higher level of security while preventing illegal access. The test results showed that the system was able to encrypt and decrypt transaction data in real-time, as well as display transaction results in the form of digital notes on deposit and balance withdrawal activities. In addition, performance tests using GTmetrix showed that the application has excellent speed, stability, and processing efficiency, making it feasible to be widely implemented in Pancadaya Waste Bank operations.